Genesis 4:17-24: A Case-Study in Eisegesis - Paul, Maarten J. (Tyndale bulletin, 1996)
This article summarises both ancient and modern interpretations of Genesis 4:17- 24, paying particular attention to the relatively unknown Jewish exegesis of this pericope. Usually there is a relation between the social and cultural position of the exegete and his positive or negative view of the technical achievements of Cain and his posterity. After a long period of negative interpretation, Calvin is the first to establish another outlook. In this century the discussion between J. Gabriel and C. Westermann reveals many motifs.